Small molecule modulation of the large-conductance calcium-activated potassium channel suppresses salicylate-induced tinnitus in mice - Scott, Luisa L.; Lowe, Andrea S.; Brecht, Elliott J.; Franco-Waite, Luis; Walton, Joseph P. (Frontiers in Neuroscience, 2022)
Tinnitus is the phantom perception of sound that has no external source. A neurological signature of tinnitus, and the frequently associated hyperacusis, is an imbalance between excitatory and inhibitory activity in the central auditory system (CAS), leading to dysregulated network excitability. The large conductance, calcium-activated potassium (BK) channel is a key player in pre- and post-synaptic excitability through its mediation of K+ currents. Changes in BK channel activity are associated with aberrant network activity in sensory regions of the CNS, raising the possibility that BK channel modulation could regulate activity associated with tinnitus and hyperacusis. To test whether BK channel openers are able to suppress biomarkers of drug-induced tinnitus and hyperacusis, the 1,3,4 oxadiazole BMS-191011 was given to young adult CBA mice that had been administered 250 mg/kg sodium salicylate (SS). Systemic treatment with BMS-191011 reduced behavioral manifestations of SS-induced tinnitus, but not hyperacusis, probed via the gap-in-noise startle response method. Systemic BMS-191011 treatment did not influence SS-induced increases in auditory brainstem response functions, but local application at the midbrain did suppress SS-suppressed spontaneous activity of auditory midbrain neurons, particularly in the frequency region of the tinnitus percept. Thus, action of BMS-191011 in the auditory midbrain may contribute to the reduction in a behavioral measure of tinnitus. Together, these findings support the utility of BK channel openers in reducing central auditory processing changes that support the formation of the tinnitus percept.